Characterization of MaltOBP1, a Minus-C Odorant-Binding Protein, From the Japanese Pine Sawyer Beetle, Monochamus alternatus Hope (Coleoptera: Cerambycidae) - Zhang, Fangmei; Merchant, Austin; Zhao, Zhibin; Zhang, Yunhui; Zhang, Jing; Zhang, Qingwen; Wang, Qinghua; Zhou, Xuguo; Li, Xiangrui (Frontiers in Physiology, 2020)
Insect Odorant-Binding Proteins (OBPs) play crucial roles in the discrimination, binding and transportation of odorants. Herein, the full-length cDNA sequence of Minus-C OBP1 (MaltOBP1) from the Japanese pine sawyer beetle, Monochamus alternatus, was cloned and analysed. The results showed that MaltOBP1 contains a 435 bp open reading frame (ORF) that encodes 144 amino acids, including a 21-amino acid signal peptide at the N-terminus. The matured MaltOBP1 protein consists of six 𝛼-helices, creating an open binding pocket, and two disulfide bridges. Immunoblotting results showed that MaltOBP1 was highly expressed in antenne and followed by wings and legs in both sexes. Fluorescence assays demonstrated that MaltOBP1 protein exhibited high binding affinity with (R)-(+)-ɑ-pinene, (-)-β-pinene, trans-caryophyllene, (R)-(+)-limonene and (−)-verbenone, which are the main voliatile compounds of the pine tree. Our combined results suggest that MaltOBP1 plays a role in host seeking behavior in M. alternatus.